Characterization of the impacts caused by ecotourism in Cachoeira da Santa, Catas Altas (MG) (Research, Society and Development, 2019)
Ecotourism is a result of sustainable tourism, which enables the development of tourism activities in contact with nature, encouraging cultural and environmental preservation. However, this activity can have negative and positive impacts where it is developed. Thus, this research aimed to evaluate the infrastructure and the impacts triggered by tourism in Cachoeira da Santa, in Catas Altas (MG). For that, a field research and a guided observation were used, covering aspects related to the characterization of the infrastructure available for the development of tourism. It was noticed that access to Cachoeira da Santa, in despite there are signs, they are badly posted. There is not a suitable parking area. Several negative impacts were seen in the study area, such as erosion and landslides along the access road to the waterfall, improper disposal of residues, bonfire remnants, and damage in rocks. Given the problems found, the compulsory measures are the definition of the parking area, besides the development of environmental education programs for tourists and residents. Thus, it highlights the utmost importance of a tourist planning so that the ecotourism does not cause negative impacts, also seeking the optimization of those impacts considered positive.